Trombocitopenia con trombosis inducida por heparina. - E Raez Luis (Revista Médica Herediana, 1996)
Heparin induced thrombocytopenia with thrombosis (HITTS) is a syndrome with broad spectrum of clinical features that has been diagnosed with more frequency. Up to 5% of patients exposed to heparin develop some type of manifestations. The etiology is probably related with the development of antibodies against a complex between heparin and platelet factor 4. The mortality is close to 25% in-patients who develop the thrombotic spectrum of the syndrome. This is a review about HITTS and the new alternatives for anticoagulation in experimentation today.